Analisis Postur Kerja Karyawan Pada Proses Pemotongan Kain Di UD Wijaya - Ardin Ardiansyah; Deny Andesta (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
UD. Wijaya is manufacturing bag products that was established in 2016. Currently, cloth cutting activities at UD Wijaya still use human labor manually. The cloth cutting activities are carried out with the work position bent and the legs bend so that workers often feel pain in the waist, back, calves, knees, ankles, and soles of the feet. In addition, there are no facilities in the form of tables or chairs for cutting places. Activities at UD wijaya is carried out for analysis of the worker's posture to find out the complaints felt in the workers' muscles in the cutting section and can provide recommendations for improving work methods or tools to minimize the risk of worker injury. Based on the analysis of employee work posture in the fabric cutting process using the Rapid Entire Body Assessment (REBA) method, a high REBA score of 9 was obtained and corrective action was needed. If the posture is not corrected immediately, then the workers may have injuries of Musculoskeletal Disorders (MSDs) in the long and short term. The working posture repairment suggested is by making tools in the form of chairs and work tables with the anthropometric data of workers.